2018
DOI: 10.7717/peerj.4318
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation resistance: effect of cuticular hydrocarbons and water content inDrosophila melanogasteradults

Abstract: BackgroundThe insect cuticle covers the whole body and all appendages and has bi-directionnal selective permeability: it protects against environmental stress and pathogen infection and also helps to reduce water loss. The adult cuticle is often associated with a superficial layer of fatty acid-derived molecules such as waxes and long chain hydrocarbons that prevent rapid dehydration. The waterproofing properties of cuticular hydrocarbons (CHs) depend on their chain length and desaturation number. Drosophila C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
(61 reference statements)
8
40
0
Order By: Relevance
“…Likewise, it has previously been demonstrated that diet does control the efficiency of the outward barrier, probably by influencing the amounts and, importantly, the composition of CHCs (Fedina et al, 2012). In line with this work, a recent study reported that the proportion of desaturated CHCs defines the efficiency of the barrier against desiccation (Ferveur et al, 2018).…”
Section: Interactions Between Sex and Dietsupporting
confidence: 70%
“…Likewise, it has previously been demonstrated that diet does control the efficiency of the outward barrier, probably by influencing the amounts and, importantly, the composition of CHCs (Fedina et al, 2012). In line with this work, a recent study reported that the proportion of desaturated CHCs defines the efficiency of the barrier against desiccation (Ferveur et al, 2018).…”
Section: Interactions Between Sex and Dietsupporting
confidence: 70%
“…Nevertheless, similar correlative effects with environmental factors have been found, with the total amount of n-alkenes showing a positive correlation with temperature and n-alkanes showing a negative correlation with humidity (Woodrow et al 2000). Moreover, it has recently been demonstrated in Drosophila fruit flies that increased proportions of n-alkenes and alkadienes are linked to increased resistance to desiccation, hinting at similar adaptive mechanisms for n-alkenes as in L. humile, allowing for acclimatization to related climatic conditions (Ferveur et al 2018).…”
Section: Discussionmentioning
confidence: 55%
“…For the corresponding correlation graphs and test statistics of each of the individual CHCs see Supplementary Fig. 2 and Supplementary Table 1 2015; Ferveur et al 2018). Trimethyl alkanes, on the other hand, showed the reverse correlation, being negatively correlated with monthly average temperature, but positively with monthly average precipitation (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported recently that desiccation susceptibility in adult D. melanogaster is due to a general physiological constitution involving Desat1 function rather than directly depending on desaturation of surface CHCs (Ferveur, Cortot, Rihani, Cobb, & Everaerts, ). To test for this possibility in our experiments, we determined the water content of control ( n = 398) and CAY10566‐fed larvae ( n = 412).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Desat1 is essential for viability. It is expressed at all stages and is among others involved in the synthesis of desaturated CHCs (Ferveur et al, ; Wang et al, ). Interestingly, the cuticle barrier efficiency depends on the ratio of desaturated to saturated CHCs, rather than on the total amounts of desaturated CHC.…”
Section: Discussionmentioning
confidence: 99%